From Ritual Communication to Convivial Entertainment: Reflections of Old Drinking Rituals in Folk Songs - Ivanauskaitė-Šeibutienė, Vita (Studia mythologica Slavica, 2022)
The article considers changes in drinking rituals and how they are reflected in folklore. Belarusian and Lithuanian songs sharing several similarities are selected for a more detailed discussion. The song motifs analysed in the article show clear links between drinking rituals and folklore (wedding songs and betrothal drinking customs), along with a certain implicit cultural link between the old ritual attitudes and festivities in subsequent times (motifs of feast songs paraphrased in drinking traditions). The theoretical framework of the paper is supported by research from the fields of folklore, ritual communication, and the history of traditional beverages that examines the cultural continuity of community life phenomena. The experiences of ritual attitudes passed down from generation to generation may encourage the existence of archaic cultural forms, even when specific ritual practices have long died out and become irrelevant as people’s life circumstances have changed significantly.